Designing Self-Adaptive Embedded Real-Time Software -- Towards System Engineering of Self-Adaptation - Rammig, Franz J.; Grösbrink, Stefan; Stahl, Katharina; Zhao, Yuhong (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
Upcoming interlinked embedded systems will be confronted with unexpectedly changing environments, which makes online adaptation without manual interference necessary. There is a need for appropriate system architectures and novel design approaches. In this paper, we discuss general concepts of self-adaptive real-time systems. Furthermore, specific system engineering techniques solving two important aspects of such a paradigm are presented. We discuss how the necessity for adaptation can be identified using Online Model Checking and how self-adapting safety guards can be designed by means of Artificial Immune Systems. Finally, we present an approach to integrating these techniques into an underlying platform architecture based on mixed-criticality virtualization.